Efficiency of organic substrates not development of manjericão(Ocimum basilicumL.)/Eficiência de substratos orgânicos no desenvolvimento do manjericão (Ocimum basilicumL.) - Jecilãine Efigênia da Silva; Rodrigo de Almeida Pinheiro; João Pedro Ferreira Barbosa; Maria Jéssica dos Santos Cabral; Daniel Rocha Santos; Rubens Pessoa de Barros (Diversitas Journal, 2020)
Basil, an annual herbaceousplant with the scientific name Ocimum basilicumL. belonging to the Lamiaceae family, is grown in Brazil with the aim of selling its leaves that can be used in natura, fresh or dried as a condiment or as a flavoring. Its cultivation constitutes an alternative generating employment and income for small farmers. The cultivation of basil has grown proportionately on the market and cultivation in different sources of fertilization in a protected environment provides significant gainsin production. the objective of this research was to evaluate the efficiency of organic substrates in the development of basil (Ocimum basilicumL.). The research was conducted during the period from April 2019 to June 2019, in greenhouse condition at theState University of Alagoas.The experimental design was completely randomized (DIC), with five treatments (T1 -sieved soil; T2-Soil + humus; T3 -Soil + bovine manure; T4-soil + goat manure; T5-soil + avian manure) and five replicates. Phenological monitoring was performed weekly, observing variables such as: plant height (AP), number of leaves (NC), stem diameter (DC), number of branches (NR) and later: Root length (CR), mass fresh (MF) and dry mass (MS). The data obtained were subjected to analysis of variance by the F test,afterwards the significant characters were subjected to the Tukey test at 5% probability using the SISVAR software 5,6. For the development of the basil, it is recommended to use the aviation bed mixed with the ground due to better results in most significant variables.